2011
DOI: 10.1093/hmg/ddr507
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein accumulates in huntingtin inclusions but forms independent filaments and its deficiency attenuates early phenotype in a mouse model of Huntington's disease

Abstract: Huntington's disease (HD) is the most common of nine inherited neurological disorders caused by expanded polyglutamine (polyQ) sequences which confer propensity to self-aggregate and toxicity to their corresponding mutant proteins. It has been postulated that polyQ expression compromises the folding capacity of the cell which might affect other misfolding-prone proteins. α-Synuclein (α-syn) is a small neural-specific protein with propensity to self-aggregate that forms Parkinson's disease (PD) Lewy bodies. Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 62 publications
2
58
0
Order By: Relevance
“…Proteasome targeting of intrabodies was initially developed for HD by Butler et al [13] using the ST14 cell model transiently transfected the mhttex1-72Q-GFP plus the huntingtin specific scFv intrabody anti-htt N17 C4-PEST to demonstrate reduction of cellular toxicity in a flow cytometry assay. Recently, in the models using transfected neurons and in vivo in HD mice, Tomas-Zapico [31] identified colocalization of microaggregates of α-Syn and N-terminal mutant htt (N-mut-htt) in the brains of R6/1 and HD94 inducible mice expressing α-Syn. Expression of N-mut-htt increased the number of α-Syn filaments, while knocking out α-Syn decreased the number of N-mut-htt aggregates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasome targeting of intrabodies was initially developed for HD by Butler et al [13] using the ST14 cell model transiently transfected the mhttex1-72Q-GFP plus the huntingtin specific scFv intrabody anti-htt N17 C4-PEST to demonstrate reduction of cellular toxicity in a flow cytometry assay. Recently, in the models using transfected neurons and in vivo in HD mice, Tomas-Zapico [31] identified colocalization of microaggregates of α-Syn and N-terminal mutant htt (N-mut-htt) in the brains of R6/1 and HD94 inducible mice expressing α-Syn. Expression of N-mut-htt increased the number of α-Syn filaments, while knocking out α-Syn decreased the number of N-mut-htt aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…The number of RFP positive htt foci in the presence of mutant A53T-Syn was significantly reduced by VH14PEST (S2 Fig). It is possible that polyQ expression may overwhelm the cellular folding machinery and α-Syn may add to the stress [31]. It is also possible that these two proteins may be competing for the lysosomal degrading machinery (Ravikumar [30, 4345].…”
Section: Discussionmentioning
confidence: 99%
“…Aggregates of HTT have also been shown to stain for α-Syn [91]. It appears that this is not owing to heterologous oligomers, but to smaller aggregates of mHTT and oligomeric (or fibrillar?)…”
Section: Interactions Between Misfolded Proteinsmentioning
confidence: 99%
“…In vivo, there are clear effects on the onset and progression of HD with manipulations of α-Syn levels. HTT transgenic mice show an earlier onset and death when crossed to α-syn overexpression transgenic mice, while expressing the HTT transgene in mice that lack the α-Syn gene slows the HTT phenotype [91,93]. Although there is still much work to be done with the genetic epidemiology to determine if known α-Syn promoter polymorphisms are modifiers for the human HD phenotype, and if the size of the CAG repeat in HTT and additional trinucleotide repeat proteins can affect PD risk, these emerging data suggest that there may be an option for using therapies directed against one misfolding protein to modify the disease course in another.…”
Section: Interactions Between Misfolded Proteinsmentioning
confidence: 99%
“…For example, it was found that polyQ inclusions in HD and other polyQ disorders are immunopositive for α -syn; after this observation it was speculated that α -syn might be recruited as an additional mediator of polyQ toxicity; the hypothesis was confirmed because the accumulation of α -syn in polyQ inclusions was found in HD postmortem brains and in the R6/1 mouse model of HD. It was also found that N-terminal mutant huntingtin (N-mutHtt) and α -syn form independent filamentous microaggregates in R6/1 mouse brain as well as in the inducible HD94 mouse model and that N-mutHtt expression increases the load of α -syn filaments [88]. In the same direction, however, using a bimolecular fluorescence complementation assay, it was found that the initial steps of the coaggregation of Htt and α -syn it was found that HTT (exon 1) oligomerized with α -syn and sequestered it in the cytosol.…”
Section: Cross Talk Between α-Synuclein and Huntingtinmentioning
confidence: 99%